KESESUAIAN TIPE KEPRIBADIAN DENGAN PEKERJAAN SEBAGAI GURU DAN HUBUNGANNYA DENGAN KINERJA GURU - Ismira Ismira (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2016)
Personality type is one of the factors that influence the effectiveness  of individuals  in  work.  If someone  gets  a job  based  on his personality  type,  then people  will feel happy proficiency  level,  effective  and productive  in their work. Teacher is a job that many acted by the community. Teachers have a very strategi c role in efforts  to achieve  goal  of National  Education.  Problems  occurred,  many teachers do not have the type of personality that fit the job as a teacher. This will affect the effectiveness of teacher performance and of course will affect the quality of graduates. This study aims to describe the suitability of the type of personalit y to work as a teacher, describing the performance of teachers and describe personality types contribute to the improvement of teacher performance. Research using quantitative methods with Simple Regression Analysis Technique.  Research tools using   an   inventory   t ype   of   personality   John   L.   Holand   and   performance questionnaire with Likert scale.